Assessment of topical versus oral ivermectin as a treatment for head lice. Issue 5 (12th July 2014) - Ahmad, Hesham M.; Abdel‐Azim, Eman S.; Abdel‐Aziz, Rasha T.
Abstract Many medications are available for treatment of pediculosis capitis including ivermectin. Our aim is to compare the efficacy and safety of topical versus oral ivermectin in treatment of pediculosis capitis. Sixty‐two patients with proved head lice infestation were included and divided into group I (31 patients; received single topical application of 1% ivermectin) and group II (31 patients; received single dose of oral ivermectin). Treatment was repeated after 1 week for nonresponders. At 1 week after treatment, the eradication rates and improvement of pruritus were significantly higher among patients who received topical than oral ivermectin. When a second treatment, topical or oral, was given to nonresponders, the cure rates of infestation and pruritus was 100% and 97% among patients treated with topical and oral ivermectin, respectively with no significant difference between the two groups. This study suggests that both topical and oral ivermectin demonstrate high efficacy and tolerability in treatment of pediculosis capitis. However, a single treatment with topical ivermectin provides significantly higher cure of infestation and faster relief of pruritus than oral ivermectin. In addition, whether topical or oral ivermectin is used to treat head lice, a second dose is required in some cases to ensure complete eradication.